Of Algorithms, Data and Ethics: A Response to Andrew Bennett1. - Mutlu, Can E. (Millennium (03058298), 2015)
Developments in the field of Information and Communication Technologies (ICT) will have a significant impact on the way we study international relations. Opportunities related to data processing and automated reasoning that emerge through developments in complex algorithms will inevitably generate a debate on research methods in social sciences. Algorithms provide novel and innovative ways to sort and make sense of digital data. Applications of ‘big data’ and its potential uses in the social sciences remain understudied in IR. The field has not fully picked up on the potential uses of algorithmic processing for research. This article looks at the ethical questions that arise from the use of algorithmic data processing and automated reasoning. In particular, the article asks whether there should be any ethical limitations on the ways we collect data to be processed by algorithms.